'Moi aussi, alors, je serai grand-mère'. La construction de la parenté dans les familles homosexuelles. Issue 2 (3rd May 2016) - Guizzardi, Luca
ABSTRACT: Using the gift as epistemological category, the article explores the social processes of kinship formation in homosexual families. Analysing the stories of lesbian families, the article tries to explain the reason why the mothers want to have kinship networks and kinship bonds. Through kinship connections, all the members are and want to be (or don't want to be) publicly recognised as reciprocal parents of the new-born.